Accounting Students Perceptions on Factors Affecting Career Choices - Donny Dwi Cahyadi; Sari Andayani; Diah Hari Suryaningrum (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
A career as an accountant is seen as promising bright prospects because this profession provides intellectual challenges and invaluable learning experiences. This study aims to determine the reasons for the accounting profession's career selection. This study uses the variables of financial rewards, professional recognition, professional training, job market considerations, and personality as factors that influence the choice of profession, namely public accountants, management accountants, accountant educators, and government accountants. The population in this study were all accounting students of semester seven and semester five who were active at STIE Perbanas Surabaya, with a total of 225 students for semester seven and 258 students for semester five. Research samples with non-probability techniques. The data of this study are primary data obtained from distributing questionnaires. Kruskal Wallis analysis technique is used to test the proposed hypothesis. Based on the test results, it was concluded that accounting students who chose the profession as public accountants, management accountants, educator accountants, and government accountants had different perceptions about the factors of financial rewards, professional recognition, professional training, and job market considerations. However, there was no difference in the perception of the personality.